Seed‐Assisted Growth of Methylammonium‐Free Perovskite for Efficient Inverted Perovskite Solar Cells. Issue 5 (9th March 2022) - Wang, Pengjiu; Chen, Xu; Liu, Tianyu; Hou, Cheng‐Hung; Tian, Yue; Xu, Xuehui; Chen, Zeng; Ran, Peng; Jiang, Tingming; Kuan, Chun‐Hsiao; Yan, Buyi; Yao, Jizhong; et al.
Abstract: The traditional way to stabilize α‐phase formamidinium lead triiodide (FAPbI3 ) perovskite often involves considerable additions of methylammonium (MA) and bromide into the perovskite lattice, leading to an enlarged bandgap and reduced thermal stability. This work shows a seed‐assisted growth strategy to induce a bottom‐up crystallization of MA‐free perovskite, by introducing a small amount of α‐CsPbBr3 /DMSO (5%) as seeds into the pristine FAPbI3 system. During the initial crystalization period, the typical hexagonal α‐FAPbI3 crystals (containing α‐CsPbBr3 seeds) are directly formed even at ambient temperature, as observed by laser scanning confocal microscopy. It indicates that these seeds can promote the formation and stabilization of α‐FAPbI3 below the thermodynamic phase‐transition temperature. After annealing not beyond 100 °C, CsPbBr3 seeds homogeneously diffused into the entire perovskite layer via an ions exchange process. This work demonstrates an efficiency of 22% with hysteresis‐free inverted perovskite solar cells (PSCs), one of the highest performances for MA‐free inverted PSCs. Despite absented passivation processes, open‐circuit voltage is improved by 100 millivolts compared to the control devices with the same stoichiometry, and long‐term operational stability retained 92% under continuous full sun illumination. Going MA‐free and low‐temperature processes are a new insight for compatibility with tandems or flexible PSCs. Abstract : Adopted seed‐assisted growth strategy to induce high crystalline, low‐bandgap FAPbI3 ‐based perovskite below the thermodynamic phase‐transition temperature (at 100 °C). The α‐CsPbBr3 seeds directly induce hexagonal α‐FAPbI3 crystals during the very initial crystallization period even at ambient temperature. Meanwhile, CsPbBr3 seeds supplied an oriented template for the following perovskite grains bottom‐up growth. The power conversion efficiency reached 22% in methylammonium‐free inverted perovskite solar cells.